European eel (Anguilla anguilla) time series ... - Gavioli, Anna; Aschonitis, Vassilis; Lanzoni, Mattia; Castaldelli, Giuseppe (Zenodo, 2024)
This dataset was managed for the aims of the project ECOSISTER (Ecosystem for Sustainable Transition in Emilia-Romagna), WP3 of Spoke 5 and provides the long-term records (from 1781 to 2013) of European eel (Anguilla anguilla L.) production in the Comacchio Lagoon (Italy). he European eel spends most of its life as a yellow eel in freshwater, brackish, and coastal environments. Upon reaching sexual maturity, it undergoes metamorphosis into a silver eel and migrates back to the Sargasso Sea to spawn and die. The silver eels of Comacchio Lagoon were always caught in the lavorieri with approximately 100% efficiency and official estimates of the total biomass were being made every year for more than 200 years. The Regional Park of the Po Delta and the Management Agency for the Parks and Biodiversity of Delta del Po were founded in 1988 and took over the infrastructures, official documents and records of the previous company managing the fishery. These fishery historical records were organized and combined with ...